Perang sebagai Fenomena Sosial Budaya: Perspektif dan Konseptualisasi Kriminologis dengan Studi Empiris di Ukraina - Sokurenko, Vitalii; Hanenko, Ihor; Orlov, Yurii; Korotiuk, Mykhailo; Kritsak, Ivan (Syariah: Jurnal Hukum dan Pemikiran, 2024)
This research delves into the sociocultural phenomenon of war, focusing on Russia's illegal invasion of Ukraine. It examines war through a criminological lens, aiming to understand its short and long-term effects on society. Through empirical analysis of Ukraine's management of the crisis, the study evaluates how the socio-cultural perspective influences war handling. Destructive consequences such as increased stress levels and migration, alongside constructive factors, are identified. The research highlights the criminogenic potential of war trauma and post-war syndrome. Despite various methods and hypotheses, socio-cultural effects persist, posing a complex challenge for Ukraine. War is portrayed as a multifaceted phenomenon influenced by demographic, economic, and ideological factors, as well as historical legacies. Ultimately, the conclusion underscores the irreparable impact of war on the environment, populations, and international relations. This suggests a pressing need for comprehensive efforts to mitigate the long-term consequences of war and foster stable post-conflict societies.